Physical activity and sport practice to improve balance control of visually impaired individuals: a narrative review with future perspectives - Carretti, Giuditta; Manetti, Mirko; Marini, Mirca (Frontiers in Sports and Active Living, 2023)
Visual disability negatively impacts balance, everyday self-efficacy, and mobility and often leads affected subjects to perceive physical exercise as a burdensome challenge thus discouraging them from practicing. Despite the well-proven benefits of regular physical activity in visually impaired people, especially addressing postural control, there are no specific guidelines and most of the available literature seems to be flawed by critical issues. Given the wide heterogeneity and the multidimensional needs of this population, a more realistic and target-specific perspective is needed in order to properly investigate and promote exercise practice and adherence for balance improvement. On this basis, through a critical overview of the recent literature, the present article aimed to enrich the current knowledge about this topic by providing innovative suggestions, both practical and methodological, and specifically deepening the disability-related deficits and peculiarities of different age ranges. Moreover, since a multidisciplinary approach is advisable when designing and leading exercise protocols tailored to visually impaired individuals, such innovative hints also highlighted the central role of the adapted physical activity specialist, hence contributing to foster its official professional recognition and involvement in this field.